Overcoming the Obstacles of Peace Education through Wellbeing Practices - Bengü, Elif; Bilgin, Gülistan Gursel (Adıyaman Üniversitesi, 2021)
A growing body of literature reports structural, cultural, social, and political barriers making_x000D_ it challenging and stressful to integrate peace education in teacher education and in-service_x000D_ teacher education programs. To support peace educators in achieving what they stand for, this_x000D_ study proposes integrating wellbeing practices and approaches into the curricula. Drawing_x000D_ from the fields of peace education, educational leadership and policy studies and higher_x000D_ education, this study examines wellbeing as a potentially promising scholarly field to support_x000D_ peace education scholarship. For happiness and life satisfaction, wellbeing links a person's_x000D_ physical, mental, emotional and social health factors not just to internal factors such as_x000D_ optimism, resilience and self-esteem but also external factors such as income, satisfaction at_x000D_ work and social networks. In order to explore the ways wellbeing can contribute to peace_x000D_ education, we first expand on peace education as a controversial and challenging practice_x000D_ especially for practitioners in the field. Next, we discuss wellbeing practices as they relate to_x000D_ educational settings. Finally, we discuss that peace educators can be supported by wellbeing_x000D_ practices to overcome the degrading and demotivating effects of their practices.
Keywords: Peace education; higher education; wellbeing; teacher training; pedagogy.; Sosyal Çalışma; Etik; Eğitim, Eğitim Araştırmaları